2022
DOI: 10.54986/irjee/2022/jul_sep/198-202
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Behaviour of Turmeric Farmers in Kadapa District of Andhra Pradesh

Abstract: The present study was carried out purposively in Kadapa district of Andhra Pradesh during the year 2020-21 as it is having the maximum area under turmeric cultivation. The main objective of the study was to analyze the marketing behavior of turmeric farmers. The study followed Ex post facto research design. The purposive sampling technique was administered and two mandals namely Mydukur and Duvvur were selected on the basis of maximum area under the turmeric cultivation and data were collected from a randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The entrepreneurial components or factors like innovativeness, achievement motivation, decision making ability, risk ability, leadership ability. Table 3 revealed that majority of farmers believe that innovativeness (82%) is the key and very important factor, followed by (80%) risk bearing ability This results support with fi nding (Sravani et al, 2022) that all the components innovativeness, achievement motivation, decision making ability similar results were reported by (Channal and Natikar, 2022) risk ability, leadership ability was found to be signifi cant. Table 6 show that easy availability of planting material (mean score 4.48) to be found highest followed by training provided by government (mean score 4.20), good marketing opportunity (mean score 4.10), low cost in cultivation (mean score 3.32), good demand (mean score 2.90), Subsidy provided by government (mean score 2.24), easy to cultivate (mean score 1.60) and more profi table than other crops (mean score 1.18).…”
Section: Resultssupporting
confidence: 82%
“…The entrepreneurial components or factors like innovativeness, achievement motivation, decision making ability, risk ability, leadership ability. Table 3 revealed that majority of farmers believe that innovativeness (82%) is the key and very important factor, followed by (80%) risk bearing ability This results support with fi nding (Sravani et al, 2022) that all the components innovativeness, achievement motivation, decision making ability similar results were reported by (Channal and Natikar, 2022) risk ability, leadership ability was found to be signifi cant. Table 6 show that easy availability of planting material (mean score 4.48) to be found highest followed by training provided by government (mean score 4.20), good marketing opportunity (mean score 4.10), low cost in cultivation (mean score 3.32), good demand (mean score 2.90), Subsidy provided by government (mean score 2.24), easy to cultivate (mean score 1.60) and more profi table than other crops (mean score 1.18).…”
Section: Resultssupporting
confidence: 82%
“…Hence, they might have suggested providing logistics and transport facilities at a reasonable cost. Sravani et al (2022) [19] stressed the importance of designing effective strategies, including training programs, demonstrations, and the development of regulated marketing policies such as Minimum Support Price, along with provisions for storage facilities. Marbaniang et al (2020) [20] accentuated the importance of enhancing agricultural marketing systems with price information, technology transfer, and strong linkages for broader market access, emphasizing the need for intensified research and innovation in marketing policies and technologies.…”
Section: Suggestions Expressed By the Respondents To Overcome Constra...mentioning
confidence: 99%